Pengaruh Latar Belakang Pendidikan, Pengetahuan Akuntansi Dan Pengalaman Kerja Terhadap Kualitas Laporan Keuangan (Pada Badan Pengelolaan Keuangan Dan Aset Daerah Provinsi Sumatera Barat) - Suci Az Zahra Zahra; Indrayeni Indrayeni (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This study aims to determine the effect of educational background, accounting knowledge and work experience on the quality of financial reports at the Regional Financial and Asset Management Agency of West Sumatra Province The population in this study were all employees of the Regional Financial and Asset Management Agency of West Sumatra Province with a total of 76 people. The sampling method used is the census taking technique or known as saturated sampling. The data analysis techniques used are descriptive statistical analysis, Data Quality Test, Classical Assumption Test, Multiple Linear Regression Test, Hypothesis Test, Coefficient of Determination. The research results show that educational background does not partially have a significant effect on the quality of financial reports. Accounting knowledge partially has a significant effect on the quality of financial reports. Work experience partially has a significant effect on the quality of financial reports. Educational background, accounting knowledge and work experience simultaneously influence the quality of financial reports at the Regional Financial and Asset Management Agency of West Sumatra Province